TARIAN POMONTE DALAM KEHIDUPAN MASYARAKAT SUKU KAILI DI DESA SIDOLE TIMUR KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - Sudirman (Kinesik, 2023)
The aim of the study was to describe the meaning of the Pomonte dance song along with the meaning of the pomonte dance in the life of the Kaili tribe in Sidole Timur Village and describe the preservation of the Pomonte dance in Sidole Timur Village Ampibabo District. The research method used is qualitative descriptive with library techniques, observation, interviews, documentation, verification, and data analysis. Based on the results of the study, the poem Pomonte dance tells how the process of planting rice, caring for it from pest attacks can damage plants, until the harvest stage until the implementation of the No Vunja custom. The meaning of the Pomonte dance is as a tradition of gratitude for the harvest that is obtained by making a celebration of a joint meal party. In addition, through the Pomonte dance, the profession of the Kaili community generally works as a rice farmer and the people who work together to help with the harvesting process, and through Pomonte dance can strengthen friendship among fellow citizens. The efforts made to maintain this Pomonte dance are by displaying it in various activities such as certain events. This is done so that the culture that is owned is not really extinct, even though it has undergone a shift, which is caused by technological developments, for example: people used to process rice into rice to pound using Nonju with mortar as a container and Yalu as a spice.